2014
DOI: 10.1073/pnas.1406107111
|View full text |Cite
|
Sign up to set email alerts
|

LEOPARD syndrome-associated SHP2 mutation confers leanness and protection from diet-induced obesity

Abstract: LEOPARD syndrome (multiple Lentigines, Electrocardiographic conduction abnormalities, Ocular hypertelorism, Pulmonary stenosis, Abnormal genitalia, Retardation of growth, sensorineural Deafness; LS), also called Noonan syndrome with multiple lentigines (NSML), is a rare autosomal dominant disorder associating various developmental defects, notably cardiopathies, dysmorphism, and short stature. It is mainly caused by mutations of the PTPN11 gene that catalytically inactivate the tyrosine phosphatase SHP2 (Src-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 51 publications
5
55
0
1
Order By: Relevance
“…This mouse model recapitulates the aggressive form of HCM found in patients carrying the same SHP2 mutation. Importantly, all our prior findings in the Q510E-SHP2 model are consistent with the HCM phenotype described in other NSML models based on Y279C and T468M mutations in SHP2 (30,45). Because of the severity and early onset of the cardiac phenotype, the Q510E-SHP2 mouse model is ideally suited for proof-of-principle studies.…”
supporting
confidence: 86%
“…This mouse model recapitulates the aggressive form of HCM found in patients carrying the same SHP2 mutation. Importantly, all our prior findings in the Q510E-SHP2 model are consistent with the HCM phenotype described in other NSML models based on Y279C and T468M mutations in SHP2 (30,45). Because of the severity and early onset of the cardiac phenotype, the Q510E-SHP2 mouse model is ideally suited for proof-of-principle studies.…”
supporting
confidence: 86%
“…Lower BMI values were also reported in children with NS by Malaquias et al (15) and, in line with these data, a survey showed that adults with NS rarely develop overweight or obesity (33). This suggested that NS-associated mutations could modify energy metabolism regulation, and this hypothesis has been recently confirmed in a mouse model expressing a NSML-PTPN11 (loss-of-function) mutation (34). NSML mice display a lean phenotype associating reduced adiposity with resistance to diet-induced obesity and improved carbohydrate metabolism, which could be converted by the inhibition of RAS/MAPK and PI3K signaling pathway activation, respectively.…”
Section: :5supporting
confidence: 59%
“…Both NSML and NS mutations facilitate the open conformation and lead to enhanced interaction of SHP2 with binding partners, including cell membrane receptors and scaffolding adapters (20). However, whereas NS mutations are gain of function (GOF) and potentiate SHP2 phosphatase activity (21)(22)(23)(24)(25)(26), all NSML mutations identified so far affect conserved residues important for PTP catalysis and are loss of function (LOF) for the phosphatase activity (20,(27)(28)(29)(30).…”
Section: Y279c/y279cmentioning
confidence: 99%